Bibliometric Analysis of Child Marriage Issues in Scopus and WoS Databases (1999-2024) - Sari, Qurnia Indah Permata (ARISTO, 2025)
This study aims to identify gender injustice in child marriage through a literature review and bibliometric approach. The data analysed come from the Scopus and Web of Science databases, covering 126 journals published between 1990 and 2024. Bibliometric methods were applied using R Studio (Biblioshiny) and VOSviewer software to identify research trends, collaboration patterns, and geographical and topical distributions in the existing literature. The results show an increase in the number of publications each year, with the United States, India, and the United Kingdom being the countries with the highest research contributions.Â  Author analysis identified Koski A, Na N, and Sethi D as the most productive authors. At the same time, McGill University and Mashhad University of Medical Sciences had the highest number of publications. The study recommends several areas for further research. First, further research can conduct a more in-depth investigation into the socioeconomic impacts of child marriage, especially in high-risk regions. Second, Multidisciplinary research involving the legal field to strengthen regulations, the health field to mitigate reproductive impacts, the education field to encourage access to learning, and the economy for family empowerment can provide a comprehensive and sustainable solution to the issue of child marriage.